SOLID EYELINER FORMULATION CONTAIN CLITORIA TERNATE L. EXTRACT IN PH ACID AND ALKALI AND IN VIVO IRRITATION TEST - Linawaty Lee; Ratna Djamil; Deni Rahmat (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Clitoria ternatea flowers contain blue anthocyanin that has potential as natural coloring. The purpose of this study was to obtain an eyeliner product containing natural coloring that is safe, stable, and can replace hazardous chemicals. Clitoria ternatea flowers were extracted by kinetic maceration with 70% ethanol. The obtained extract was subjected to standard quality tests, phytochemical screening, and determination of total anthocyanin content and antioxidant activity (DPPH assay). Eyeliner-containing extracts were prepared in three pH variations (acidic, neutral, and alkaline). These three types of eyeliner preparations were subjected to an irritation test on shaved male albino white rabbit skin. stability test using the cycle test method, hardness, break point, and melting point were also performed. The results showed that Clitoria ternatea extract contains 0.2187% anthocyanin, has an antioxidant activity IC50 of104.7 Âµg/mL, and is free of heavy metals. The eyeliner contained Clitoria ternatea extract was dark blue when applied to the skin. Eyeliner preparations were stable in three stability cycle tests. The irritation test on the male albino rabbit skin showed no irritation. Clitorial ternatea extract can be used as natural coloring in eyeliner preparation. Keywords: Butterfly pea, Clitoria ternatea L., Anthocyanin, Antioxidant, Eyeliner.